Perspectives on financing healthcare in Africa - Dube, Samukeliso (My University, 2016)
Following decades of under-investment, gaps in Africa’s healthcare infrastructure are becoming disturbingly obvious. The interplay of governments’ fiscal policies of budget imbalance reduction and other political considerations present a seemingly insurmountable obstacle to overcoming the backlog in Africa’s healthcare infrastructure. The two main objectives of this study were to understand the sources of financing and the best way to structure the financing of healthcare infrastructure in Africa. Looking at financing arrangements in various industries; and how healthcare sectors in developed countries have been financed, the report draws on perspectives from the financiers on how the healthcare infrastructure gap should be filled in Africa. This study, which utilised survey questionnaires and in-depth interviews, identified government revenues, regional development banks, private equity and donor financing numbers as dominant funding sources for the financing of healthcare infrastructure in Africa. Further, the study explored various ways in which finance could be structured and found that within those various models of financing, donor financing and government revenue were statistically significant on structuring the finance, especially within public-private partnership arrangements. These include sale and lease back arrangements (p=0.0022), complete ownership of projects by the private sector (p=0.003), management operation contracts (p=0.00034) and other forms of PPPs. More perspectives were obtained on enablers and barriers to improving investability of the healthcare sector. Africa’s economic growth and the improving ease of doing business were major enablers for healthcare sector’s investability. However, the role played by government as both a financier and a regulator seemed a barrier. Some structural models that would need government back-up include subordinated debt; with pricing at marginal cost and matching risk and return recovered through the taxation system. The latter continues to characterise much of Africa’s publicly provided healthcare infrastructure. In conclusion, investments in healthcare may not be separated from a country’s level of financial deepening. As the sector develops, it then becomes possible to utilise the models aforementioned. It is recommended that any governments’ investments in healthcare be more catalytic, to unlock value that allows the private sector to compete, both as financiers and innovators in healthcare. Furthermore clear strategies on PPPs are urgently needed for healthcare in Africa including policy consistency in financing and regulating healthcare.
Wits Business School University of Witwatersrand Johannesburg, South Africa Master in Finance and Investment (2014)
Keywords: Health services administration--Africa; Public health--Africa; Medical policy--Africa; Public-private sector cooperation--Africa